Political–Business Relations and Their Influence on Public Policy and Economic Governance in Bulukumba Regency - Iqbal Norr Arfah; Irwan Alim; Muhammad Amril Pratama Putra (Social and Political Corner, 2026)
This study examines the relationship between democracy and business actors within the context of local political contestation in Bulukumba Regency, Indonesia, with particular attention to economic activities in coastal areas. The research aims to analyze how business actors in key coastal sectors interact with political elites and influence democratic processes and governance practices at the local level. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, and document analysis involving political actors, community leaders, and observers of local political dynamics. The findings show that business actors play a significant role in supporting political candidates through financial contributions, social networks, and strategic alliances that strengthen their influence during electoral competition. In coastal regions where economic activities such as fisheries, marine tourism, and traditional shipbuilding dominate the local economy, these interactions often develop into patronage networks linking economic resources with political authority. Consequently, political–business relations shape democratic competition and influence governance and development priorities in coastal areas.